Health worker-related factors contributing to Delayed HealthCare Service Delivery among Health Workers at the Outpatient department of Luweero Hospital, Luwero District. A cross-sectional study. - Mwebaza, Loy Joyce; Mpamize, Habert; Nansereko, Hasifa; Naggulu, Immaculate Prosperia; Ssemuwemba, Francisco; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2026)
Background: Delayed health care service delivery significantly affects patient health outcomes. The study aimed to identify health worker-related factors contributing to Delayed HealthCare Service Delivery among Health Workers at the Outpatient department Luweero Hospital, Luwero District. Methodology: A cross-sectional quantitative descriptive study was conducted among 40 health workers at the Outpatient Department of Luwero Hospital, selected from a population of 45 staff using Krejcie and Morgan’s table. Data were collected using structured self-administered questionnaires and analyzed using frequencies and percentages in Microsoft Excel 2016. Purposive sampling was used. Validity was ensured through expert review, reliability through pretesting with 10 respondents, and ethical approval and informed consent were obtained. Results: Among the 40 respondents, most were aged 29-39 years (42.5%), had certificate-level education (45%), and were nurses (47.5%). Half of the health workers (50%) reported never receiving refresher training. Staffing was a major concern, with 50% describing staff numbers as very few and only 20% reporting adequate staffing. Heavy workload was the main factor affecting motivation for 70% of respondents, while only 7.5% cited good pay and recognition. Teamwork was rated as very good by 50%, though 17.5% described it as poor. Supervision was inadequate, as 42.5% reported that supervisors rarely checked their work or provided feedback. Job satisfaction was generally low, with 45% of respondents reporting dissatisfaction and only 15% indicating satisfaction with their jobs. Conclusion: Delayed healthcare service delivery at the facility is largely driven by staff shortages, low motivation, inadequate supervision, and poor job satisfaction. Recommendation: The hospital administration and relevant authorities should recruit more health workers to reduce workload, minimize burnout, and improve the speed of service delivery.